The Role of Language Education in Community Development: Insights from Literature Review - Sukini; Aat Ruchiat Nugraha; Wulandari, Andi Sri Rezky; Miftachul Amri; Asrul Sani; Andri Kurniawan; Bambang Mardi Sentosa (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2024)
Language education plays an important role in community development, according to our literature review. This research examines how language education can facilitate community growth and development, and how this impacts social and economic dynamics. This research is a literature analysis. A literature review was conducted of scholarly literature, academic publications and research reports related to the role of language education in various community development contexts. The study highlights the importance of language education as a tool to improve the quality of life and opportunities for community members. The results show that high-quality language education can increase awareness and appreciation of local culture and traditions, and strengthen intergenerational and inter-community connections. In addition, language education that strengthens communication and negotiation skills can facilitate access to economic opportunities, such as employment, training and investment. This research highlights the importance of language education as a tool to improve quality of life and community opportunities.